The Implementation of Group Counselling Using Self-Talk Techniques to Reduce Students' Communication Anxiety - Tara Latifah Nur Qulby; Nurussakinah Daulay (MASI Mandiri Edukasi, 2026)
Communication anxiety is a psychological problem commonly experienced by junior high school students and has an impact on learning participation, social interaction, and academic development. This study aimed to examine the effectiveness of group counselling using the self-talk technique in reducing communication anxiety among eighth-grade students at YPAK PTPN III Gunung Para Private Junior High School. This study employed a quantitative, quasi-experimental design with a nonequivalent control group. The research sample consisted of 16 students who had high levels of communication anxiety, comprising 8 students in the experimental group and 8 students in the control group, selected through purposive sampling. The research instrument was a communication anxiety scale covering mood, cognitive, somatic, and motor aspects. Data analysis was conducted using normality and homogeneity tests and a paired-samples t-test in SPSS version 27. The results showed a significant decrease in communication anxiety in the experimental group after receiving group counselling with the self-talk technique, as indicated by a p-value of 0.000 < 0.05. These findings demonstrate that group counselling using the self-talk technique is effective in reducing students' communication anxiety. This study provides theoretical contributions to strengthen the cognitive-behavioural approach and practical contributions as a reference for guidance and counselling teachers in designing effective group counselling services at the junior high school level.